A new species in the cohniella ascendens complex from amazonian Venezuela (orchidaceae, oncidiinae) - Cetzal-IX, William; Carnevali, Germán; NoGuera-Savelli, Eliana (Lankesteriana: International Journal on Orchidology, 2014)
Cohniella amazonica (Orchidaceae, Oncidiinae, Trichocentrum-clade) a species in the Cohniella ascendens complex, from Amazonas, Venezuela, is herein newly described, illustrated, and characterized based on morphological characters. The new taxon is similar to C. nuda, from which it differs in the subquadrate- oblong lateral lobes of the labellum that are in the same plane as the central lobe, the 5-partite callus, the bipartite column wings, and the distribution range restricted to the northeastern portion of Amazonas, Venezuela. The conservation status of the new taxon is assessed as Data Deficient (DD) according to the IUCN (International Union for Conservation of Nature) criteria. We provide a key and table of characters to diagnose the Cohniella ascendens species complex, a comparative figure, and a map showing the geographical distributions of the species in this group.